IMF Conditionality : Experience Under Stand-by and Extended Arrangements, Part I: Key Issues and Findings - Dicks-Mireaux, Louis (Occasional Papers; Occasional Paper, 1995)
This paper is Part I of a two-volume study conducted as a part of the IMF's ongoing process of evaluating its lending facilities. It focuses on IMF-supported programs and macroeconomic performance during 1988-92, reflecting information available through the end of 1993. Part I provides an overview of the experiences during the arrangements reviewed: it describes the initial conditions faced in these countries, the adjustment strategies adopted, the degree to which programs were implemented, and the extent of sustained adjustment experienced.